A Real-Time, Fluorescence-Based Assay for Measuring µ-Opioid Receptor Modulation of Adenylyl Cyclase Activity in Chinese Hamster Ovary Cells. (February 2014) - Knapman, Alisa; Abogadie, Fe; McIntrye, Peter; Connor, Mark
Inhibition of adenylyl cyclase (AC) activity is frequently used to measure µ-opioid receptor (MOR) activation. We sought to develop a simple, rapid assay of AC activity in whole cells that could be used to study MOR signaling. Chinese hamster ovary cells expressing human MOR (CHO-MOR cells) were grown in 96-well plates and loaded with membrane potential–sensitive fluorescent dye. CHO-MOR cells were treated with the AC activator forskolin (FSK), with or without simultaneous application of MOR agonists, and the resulting change in fluorescence was measured. CHO-MOR cells hyperpolarized in response to application of FSK ( p EC50, 7.3) or calcitonin ( p EC50, 9.4). A submaximally effective concentration of FSK (300 nM) caused a 52% ± 2% decrease in fluorescence. Simultaneous application of the opioids DAMGO ( p EC50, 7.4; Emax, 56%), morphine ( p EC50, 7.0; Emax, 61%); and buprenorphine ( p EC50, 8.6; Emax, 24%) inhibited the FSK response in a dose-dependent manner while having no effect by themselves. The effects of DAMGO were blocked by pertussis toxin. This assay represents a simple, robust method for real-time observation of AC inhibition by MOR in CHO cells. It represents an appealing alternative to end-point assays that rely on cAMP accumulation and can avoid potential confounds associated with rapid desensitization of MOR signaling.